Rural Students Conceptrons about the Environment - Bustamante-Saavedra, Olga Rocío; Ochoa-Camacho, Edelmira (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This is a research description results on environmental education, that was aimed to characterize the conceptions and beliefs of some primary school students in a rural sector, belonging to the Salamanca Technical Institution, located in the Samaca municipality, of the Boyaca Departament-Colombia, It was based on pro-environmental aspects four main categories: a) Individual concern, b) Social preoccupation, c) Confidence and d) Criterion. A specific 29 items test and a Likert responsescale (4 options), based on the article ”sca|e environmental attitudes toward specific problems"(1) was adapted. With these preliminary results it can be concluded, that there is a great individual concern in several aspects related to environmental problems.Therefore, to promote environmental education is necessary a process of values, concepts and attitudes recognition,in order to potentiate the educational strategies that generate positive social and cultural change implementation.